Fire is your water : a novel - Minick, Jim, 1964- (Swallow Press, 2017)
"Sacred chants are Ada Franklin's power and her medicine: by saying them, she can remove warts, stanch bleeding, and, especially, draw the fire from burns. At age twenty, her reputation as a faith healer defines her in her rural Pennsylvania community"--